E2F repression by C/EBPalpha is required for adipogenesis and granulopoiesis in vivo. - Porse, B; Pedersen TA; Xu, X; Lindberg, B; Wewer, U; Friis-Hansen, L; Nerlov, C (2001)
The C/EBPalpha transcription factor is required for differentiation of adipocytes and neutrophil granulocytes, and controls cellular proliferation in vivo. To address the molecular mechanisms of C/EBPalpha action, we have identified C/EBPalpha mutants defective in repression of E2F-dependent transcription and found them to be impaired in their ability to suppress cellular proliferation, and to induce adipocyte differentiation in vitro. Using targeted mutagenesis of the mouse germline, we show that E2F repression-deficient C/EBPalpha alleles failed to support adipocyte and granulocyte differentiation in vivo. These results indicate that E2F repression by C/EBPalpha is critical for its ability to induce terminal differentiation, and thus provide genetic evidence that direct cell cycle control by a mammalian lineage-instructive transcription factor couples cellular growth arrest and differentiation.